APPROACHES TO CONTROL BIOFOULING IN POTABLE WATER DISTRIBUTION NETWORKS - Kaur, Navpreet (International Journal of Research -GRANTHAALAYAH, 2025)
Water is a critical resource that sustains life and its availability should be secured.The freshwater is contaminated due to human activities and consequently is enriched in foreign and potentially dangerous species. These pollutants can be classified into biological components that include microbes (bacteria, viruses and fungi), inorganic compounds (radioactive materials and heavy metals), and organic compounds (drugs, soaps, pesticides, fertilizers, and oils)are not only harmful to human health and the environment but also induce changes in natural aqueous habitats and organisms thus affecting the water quality and ecological balance. Fulfilling the demand for clean drinking water to the general public has been a challenging task in developing countries. Among various water treatment technologies, the utilization of nano-materials and nanostructures has received significant consideration due to their sustainability and stability. The dimensions of nanomaterials impart exceptional chemical and physical properties, such as multivalent interactions with bio-molecular and cellular systems. This paves the way to treat biofouling of water with nanomaterial due to their antimicrobial properties and reduces the possibility of harmful disinfection by-products (DBPs) formation. Different types of nanomaterials that can act as nanosorbents, nanocatalysts, bioactive nanoparticles, nanostructured catalytic membranes, nanomembranes and nanoparticles (nanocelluloses) provide an efficient methodology for solving water bio fouling problems. These highly efficient nano-materials owing to the high aspect ratio, surface charge, surface area and mechanical strength can serve as remediation for biofouling of water. However, the major issue with nano-materials synthesized conventionally is their toxicity although the synthesis of nanomaterials using green routes can serve as an answer to this problem